2018
DOI: 10.1016/j.ijcha.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognostic implications of late bleeding events after percutaneous mitral valve repair

Abstract: ObjectivesMitraClip is an established therapy for patients with mitral regurgitation (MR) that are considered of high-risk or inoperable. However, late bleeding events (BE) after hospital discharge and their impact on prognosis in this cohort of patients have been poorly investigated. Our purpose is to address the incidence, related factors and clinical implications of BE after hospital discharge in patients treated with MitraClip.MethodsProspective registry of all consecutive patients (n = 80) who underwent M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…TMVR is performed via venous access, which typically is associated with lower bleeding complications compared with procedures requiring arterial access; however, there are limited contemporary data on rates of bleeding in patients undergoing TMVR. In our study one in four patients undergoing TMVR experienced a bleeding/transfusion event during the index hospitalization, which is similar to other recent investigations showing rates of 21–26% . Large‐bore venous access should be performed and managed as meticulously as arterial access to prevent access‐site bleeding complications.…”
Section: Discussionsupporting
confidence: 89%
“…TMVR is performed via venous access, which typically is associated with lower bleeding complications compared with procedures requiring arterial access; however, there are limited contemporary data on rates of bleeding in patients undergoing TMVR. In our study one in four patients undergoing TMVR experienced a bleeding/transfusion event during the index hospitalization, which is similar to other recent investigations showing rates of 21–26% . Large‐bore venous access should be performed and managed as meticulously as arterial access to prevent access‐site bleeding complications.…”
Section: Discussionsupporting
confidence: 89%
“…A prior study has demonstrated a relationship between isolated mitral valve surgery including both mitral valve repair and replacement, and gastrointestinal bleeding [7]. A similar association of gastrointestinal bleeding has been reported in over 30% of patients after the implantation of MitraClip and it has been found to be the second most common cause of bleeding complications postprocedurally following access site-related bleeding [8,9].…”
Section: Discussionmentioning
confidence: 80%
“…Those whose echocardiogram reports suggested the presence of either mechanical or bioprosthetic prostheses, in the aortic or mitral positions were included in the study. The rationale for including patients with surgical or transcatheter mitral valve repair in our cohort is that the data indicates that there is an association between these types of repairs and GI bleeding events and acquired von Willebrand disease [7][8][9]. Electronic medical records of these patients were reviewed for demographic, clinical, laboratory, and echocardiographic data.…”
Section: Study Population and Clinical Datamentioning
confidence: 99%